2014
DOI: 10.1080/21565562.2014.996025
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine control of spermatogenesis: Role of FSH and LH/ testosterone

Abstract: Evaluation of testicular functions (production of sperm and androgens) is an important aspect of preclinical safety assessment and testicular toxicity is comparatively far more common than ovarian toxicity. This chapter focuses (1) on the histological sequelae of disturbed reproductive endocrinology in rat, dog and nonhuman primates and (2) provides a review of our current understanding of the roles of gonadotropins and androgens. The response of the rodent testis to endocrine disturbances is clearly different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
206
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(215 citation statements)
references
References 197 publications
(231 reference statements)
4
206
0
5
Order By: Relevance
“…It is well established that testosterone is produced by interstitial cells (Shima et al, 2013a,b) and is essential for maintaining and stimulating normal spermatogenesis (Baker and O'Shaughnessy, 2001;Ramaswamy and Weinbauer, 2015). Bergh and Damber (1978) in a morphometric and functional investigation of the interstitial cells of experimental cryptorchidism in rats observed that interstitial cell function in the cryptorchid testis was maintained at 30 days but highly impaired at 100 days of age.…”
Section: Introductionmentioning
confidence: 97%
“…It is well established that testosterone is produced by interstitial cells (Shima et al, 2013a,b) and is essential for maintaining and stimulating normal spermatogenesis (Baker and O'Shaughnessy, 2001;Ramaswamy and Weinbauer, 2015). Bergh and Damber (1978) in a morphometric and functional investigation of the interstitial cells of experimental cryptorchidism in rats observed that interstitial cell function in the cryptorchid testis was maintained at 30 days but highly impaired at 100 days of age.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, FSH is another important regulator of Sertoli cells, stimulating virtually all functions related to spermatogenesis. Therefore, the low testosterone and FSH levels in obese men can be a cause for impaired spermatogenesis and finally lead to reduced sperm counts and subfertility (Cheng et al 2010, Ramaswamy & Weinbauer 2015.…”
Section: Obesity Leads To Hypogonadismmentioning
confidence: 99%
“…This action regulates synthesis and release of both gonadotropins, LH and FSH, that control gonadal maturation and adult reproductive physiology via stimulation of sex steroid synthesis (1). In males, FSH stimulates proliferation of immature Sertoli cells and spermatogonia, whereas LH stimulates Leydig cells to produce testosterone (4). In females, LH triggers ovulation, promotes development of the corpus luteum, and stimulates theca cells to produce androgens, whereas FSH stimulates recruitment of secondary ovarian follicles and the secretion of estradiol from granulosa cells, thereby promoting follicular maturation, which ultimately leads to ovulation (5).…”
Section: Introductionmentioning
confidence: 99%